Development of an oral push–pull osmotic pump of fenofibrate-loaded mesoporous silica nanoparticles - Zhao Z (Dove Medical Press, 2015)
Zongzhe Zhao, Chao Wu, Ying Zhao, Yanna Hao, Ying Liu, Wenming ZhaoPharmacy School, Liaoning Medical University, Jinzhou, Liaoning Province, People’s Republic of ChinaAbstract: In this study, mesoporous silica nanoparticles (MSNs) were used to prepare an oral push–pull osmotic pump. Fenofibrate, the selected model drug, was firstly loaded into the MSNs, followed by a suspending agent consisting of a drug layer of push–pull osmotic pump. Fenofibrate-loaded MSNs were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), nitrogen adsorption/desorption analysis, differential scanning calorimetry (DSC), powder X-ray diffractometry (PXRD) analysis, and Fourier-transform infrared (FT-IR) spectroscopy. Polyethylene oxide of molecular weight (MW) 100,000 and polyethylene oxide of MW 6,000,000 were selected as the suspending agent and the expanding agent, respectively. Cellulose acetate was used as the semipermeable membrane, along with polyethylene glycol 6,000 to increase the flexibility and control the membrane permeability. The in vitro dissolution studies indicated that the osmotic pump tablet combined with MSNs was able to deliver fenofibrate in an approximately zero-order manner in 24 hours. A pharmacokinetic study showed that, although the maximum plasma concentration of the osmotic pump was lower than that of the reference formulation, the relative bioavailability was increased, indicating that the osmotic pump was more efficient than the reference tablets. Therefore, using MSNs as a carrier for poorly water-soluble drugs is an effective method for preparing osmotic pump tablets.Keywords: poorly water-soluble drug, in vitro dissolution, pharmacokinetic study